Optimalisasi Pembelajaran Agama Islam Melalui Penggunaan Media Interaktif Perspektif Guru - Ula, Ahmad Nilnal Munachifdlil; Hidayati, Hanik (CENDEKIA: Jurnal Studi Keislaman, 2024)
Islamic Religious Education is an integral part of education that requires innovative and effective approaches. This study aims to optimize Islamic Religious Education through the use of interactive media from the perspective of teachers. The research method used is a case study involving ten Islamic Religious Education teachers in a secondary school in Indonesia. The results show that the use of interactive media in Islamic Religious Education can increase students' interest and understanding of the subject matter. The teachers involved in this study also indicate that the use of interactive media provides variation in teaching and helps achieve learning objectives more effectively. This study makes an important contribution to the development of more interactive and effective methods of Islamic Religious Education.